Innovation and Green Marketing: Synergistic Strategies to Promote Economic and Environmental Sustainability - Sougi, Widhia; Widodo, Sri (Dinasti Publisher, 2025)
This study looks at how innovation and green marketing work together to drive economic and environmental sustainability. Companies face enormous challenges to maintain their competitiveness and adopt environmentally friendly practices in an environment that increasingly demands sustainability. This research looks at how this synergistic method can add value, reduce environmental impact, and strengthen companies in a market increasingly concerned with sustainability. This research uses a qualitative and descriptive approach. The research results show that despite several barriers, such as greenwashing, high costs, and lack of consumer awareness, this approach can be successful. However, with supportive policies, good consumer education, and increased access to green finance, this approach can be successful. The importance of cooperation between the private sector, government and consumers in creating an ecosystem that supports the transition to a greener and more sustainable economy. Companies can achieve sustainable economic sustainability while contributing to environmental preservation by adopting green and green marketing innovations in an integrated manner.